Comparisons of ball possession, match running performance, player prominence and team network properties according to match outcome and playing formation during the 2018 FIFA World Cup - Aquino, R.; Machado, J. C.; Clemente, F. M.; Praça, G. M.; Gonçalves, L. G. C.; Melli-Neto, B.; Ferrari, J. V. S.; Palucci Vieira, L. H.; Puggina, E. F.; Carling, C. (International Journal of Performance Analysis in Sport, 2019)
This study on the 2018 Russia FIFA World Cup examined: i) the potential variations of ball possession, match running performance, player prominence, team network properties according to match outcome and playing formation; and ii) the relationships between player prominence and total distance covered according to team ball possession. Sixty-one matches were analysed (n = 988 player observations). Running performance was examined using total distance covered in (TDIP) and out of possession, and that travelled in different speed-range categories. Player prominence (micro) and team network properties (macro) were obtained using social network analysis where completed passes between teammates were counted (n = 28,019 passes). Main findings were: i) with the exception of clustering coefficients which indicate the level of interconnectivity between close teammates (win = draw > loss), match outcome was unaffected by ball possession, running and network measures; iii) teams employing a1-4-2-3-1 formation reported greater values for ball possession, TDIP, and micro/macro network measures compared to those playing 1-4-4-2 and 1-4-3-3 formations; iv) TDIP tended to be related to most player prominence variables, even though the magnitude of coefficients varied considerably according to network measures and playing positions. This study has provided additional insights into elite soccer match-play performance.